2021
DOI: 10.1038/s41467-021-25755-5
|View full text |Cite
|
Sign up to set email alerts
|

The cichlid oral and pharyngeal jaws are evolutionarily and genetically coupled

Abstract: Evolutionary constraints may significantly bias phenotypic change, while “breaking” from such constraints can lead to expanded ecological opportunity. Ray-finned fishes have broken functional constraints by developing two jaws (oral-pharyngeal), decoupling prey capture (oral jaw) from processing (pharyngeal jaw). It is hypothesized that the oral and pharyngeal jaws represent independent evolutionary modules and this facilitated diversification in feeding architectures. Here we test this hypothesis in African c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 87 publications
0
39
0
Order By: Relevance
“…We sought to examine whether shape variation follows similar patterns as volume, suggesting shared origins of variation, or whether shape and volume were unrelated. To determine morphological variation in shape across the brain, we employed shape-analysis approaches previously used in assessing morphometrics of whole brain and brain regions (28, 32, 33). We first examined whether shape showed variation between populations for regions with no variation in volume, then how volume and shape relate within specific regions and finally whether shape variations follow the same brain-wide patterns seen in volumetric variation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to examine whether shape variation follows similar patterns as volume, suggesting shared origins of variation, or whether shape and volume were unrelated. To determine morphological variation in shape across the brain, we employed shape-analysis approaches previously used in assessing morphometrics of whole brain and brain regions (28, 32, 33). We first examined whether shape showed variation between populations for regions with no variation in volume, then how volume and shape relate within specific regions and finally whether shape variations follow the same brain-wide patterns seen in volumetric variation.…”
Section: Resultsmentioning
confidence: 99%
“…Beak differences in Galapagos finches have been shown to change in accordance with the size food sources, and such changes have been shown to rely on differences in bone morphogenic protein signaling (42, 43). Craniofacial differences in African cichlids also have been shown to vary as an adaptive quality to food availability (32, 33). Furthermore, standard methods for assessing complex shape features have been applied to studying brain shape evolution in non-model organisms, generating anatomical evolutionary hypotheses that have lacked an appropriate model for assessing functional mechanisms of anatomical evolution (9, 10, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their exploratory behavior and multipotency, NCCs have been recognized as a key contributor to phenotypic plasticity and evolvability [ 11 , 12 , 15 , 117 , 118 , 119 , 120 , 121 , 122 ]. It will be interesting to understand whether changes in VENTX / NANOG and POU5 / OCT4 spatiotemporal expression or protein activity (e.g., stability/degradation, physical interactions with co-factors and/or DNA) and distribution during mitoses (asymmetric cell division) within NCCs may contribute to cellular heterogeneity and fate choice during development, as observed in PSCs [ 15 ].…”
Section: Reprogramming Capacity Of Developmental Potential Guardians ...mentioning
confidence: 99%
“…Some studies found that highly integrated structures within confined anatomical regions such as the lower jaw mapped to the same genomic region [ 26 , 27 ]. Traits previously thought to be evolutionarily decoupled such as the oral and pharyngeal jaws have also been shown to be linked genetically [ 28 ]. On the other hand, some studies mapping several functionally integrated, but anatomically separate aspects of foraging morphology [ 29 , 30 ], found minimal overlap of QTLs between the different aspects, suggesting modularity in the genetic architecture underlying these traits.…”
Section: Introductionmentioning
confidence: 99%